Health risk attributed to consumption of vegetables irrigated with different effluents containing enteric viruses via QMRA and DALY - Hasan Pasalari; Angila Ataei-Pirkooh; Mohammad Khanizadeh; Mahdi Farzadkia (Scientific Reports)
Abstract A comprehensive study was developed to estimate the disease burden (DB) caused by NoV and RoV in the effluents of different stages of wastewater treatment process used for irrigation high-consumption vegetable. The sewage samples were withdrawn from raw wastewater, primary sedimentation tank outlet, secondary clarifier outlet and effluent of largest WWTP in middle east and analyzed in terms of RoV and NoV using RT-PCR. QMRA tools and DALY index were utilized to estimate the Probability of infection (Pinf), probability of illness (Pill) and disease burden (DB) via Monte-Carlo simulation technique and R software. The mean concentration of RoV in raw wastewater (234 Virus.mL−1) experienced a decreasing trend after primary purification (136 Virus.mL−1) and secondary sedimentation (53 Virus.mL−1); the minimum concentration of RoV was found in the effluent (12 Virus.mL−1). No species of NoV were detected in raw wastewater, primary sedimentation tank, secondary sedimentation tank, and effluent. The DALY index, obtained based on the concentration of RoV in all samples of sewage exceeded the values recommended by World Health Organization (WHO) (10−6 (per person per year) (pppy)) and the United States Environmental Protection Agency (10−4 pppy). The sensitivity analysis indicated that the variation in RoV concentration and the time between the last irrigation and consumption have highest contribution on DB. Generally, this first study in the field of QMRA in wastewater treatment train can help decision makers and governing bodies to justify the health attributed to infected sewage-irrigated vegetables and find promising approach to reduce the corresponding health risk.